Nemesnyár állományok egészségi vizsgálata a Taktaközben - Porkoláb Gábor (2021)
A new type of bacterium appeared in Hungary in the second half of the 2000s, which infects noble poplar stocks. In my diploma thesis, I examined what could be the cause of this problem, and of the two poplar clones in the study area, do they uniformly damage both? The project started with field measurements, during which every fifth row was measured and symptoms were scaled, at the same time measuring breast height diameters. Sampling was followed by laboratory tests, knowing that we could find out or even narrow the range of pathogens in the herd. Dr. Katalin Tuba, my consultant, and Jenő Jakab, an engineer working in a laboratory, successfully found out that in addition to bacteria, many insects and fungi also play a role in the degradation of stocks. The results obtained after the statistical evaluations supported my previously hypothesized that the bacterium causes less damage to the ’Pannonia’ poplar than to the ’I-214’ clone. Amorpha fruticosa probably influenced the easier colony and spread of the bacterium in the poplar stock. After the research, I made a number of suggestions, so for example, it might be reasonable to have a kind of clone change in these areas, as well as to create a kind of more mosaic table structure to avoid new types of pests. It is also advisable to disinfect the tools used during pruning to reduce the spread of the bacterium. In addition, manual disinfection of propagating material may also be an option in order to work with a healthier herd in the near future. Overall, further research is needed on this topic, and it may take several years before we are able to find the best possible solution to the problem, but in my opinion, the direction is right and the goal is given, we have to preserve the health of Hungary's noble poplar stocks.